2008
DOI: 10.4141/cjas07126
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of genetic variability and inbreeding characteristics in a population of Zandi sheep

Abstract: Ghafouri-Kesbi, F., Eskandarinasab, M. and Hassanabadi, A. 2008. Investigation of genetic variability and inbreeding characteristics in a population of Zandi sheep. Can. J. Anim. Sci. 88: 409Á417. The aim of the present study was to evaluate the genetic parameters and genetic trends for birth and weaning weights, and to quantify the inbreeding characteristics for a population of Zandi sheep. Genetic parameters from both single-and two-trait analyses were estimated using restricted maximum likelihood (REML) wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The location of the experimental flock as well as their natural habitat, description, and husbandry practices were described by Ghafouri-Kesbi et al (2008).…”
Section: Datamentioning
confidence: 99%
“…The location of the experimental flock as well as their natural habitat, description, and husbandry practices were described by Ghafouri-Kesbi et al (2008).…”
Section: Datamentioning
confidence: 99%
“…Thus, one can conclude that the genetic variability within an open flock might be monitored more appropriately by using the average relatedness; even if the population is not concerned by a conservation program as argued by Oliehoek et al (2006). A similar conclusion was carried out by Goyache et al (2003) and Ghafouri-Kesbi et al (2008).…”
Section: Discussionmentioning
confidence: 73%
“…However, under the pedigree depth, more lambs are born inbred. But, with an experimental herd, where also some selection schemes were tested, the inbreeding is not avoidable (Ghafouri-Kesbi et al 2008). Nevertheless, in spite of this broad proportion, it is possible to maintain or even minimise inbreeding rate by managing the matings at each generation following specific strategy like this proposed by Sánchez et al (2003).…”
Section: Discussionmentioning
confidence: 99%
“…Populations of domestic animals with a small Ne can also exhibit reduced genetic variation compared to ancestral ones ( Ghafouri-Kesbi et al, 2008 ; Kim et al, 2013 ; Freedman et al, 2014 ; Quaresma et al, 2014 ). For example Freedman et al (2014) found that the domestication process of dogs resulted in reduced genomic variation consistent with at least a 16-fold reduction in population size.…”
Section: Introductionmentioning
confidence: 99%